2016
DOI: 10.4049/jimmunol.1600793
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Roles of Tyrosine Kinase Receptors Mer and Axl Determine Clinical Outcomes in Experimental Immune-Mediated Nephritis

Abstract: Glomerulonephritis is one of the most severe manifestations of systemic lupus erythematosus, with considerable morbidity and mortality. There remains a major unmet need for successful management of lupus nephritis. TAM family receptor tyrosine kinases (Mer and Axl) play an important role in the maintenance of immune homeostasis in the kidney. Mer is constitutively expressed in the glomeruli; Axl expression is inducible in glomeruli under inflammatory conditions. To investigate the distinct functions of Axl and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(57 citation statements)
references
References 55 publications
9
48
0
Order By: Relevance
“…2C and D). Consistent with our previous findings [19], p38MAP kinase remained undetectable in primary GECs regardless of Mer expression (data not shown). Taken together, these data suggest an inhibitory function of Mer in regulating LPS-mediated Akt and ERK1/2 expression and activation.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…2C and D). Consistent with our previous findings [19], p38MAP kinase remained undetectable in primary GECs regardless of Mer expression (data not shown). Taken together, these data suggest an inhibitory function of Mer in regulating LPS-mediated Akt and ERK1/2 expression and activation.…”
Section: Resultssupporting
confidence: 93%
“…Consistent with this, renal Mer expression, which was originally demonstrated by Northern blot [20, 21], is highest in both mice and humans in the kidney [19–21]. We confirmed renal expression of Mer protein by Western blot [19] and by immunofluorescent staining (Fig. 1B).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In the context of these possibilities, a study showed that advanced human carotid arteries were enriched in MerTK when compared with normal carotid arteries and that Protein S levels increased with advanced plaque grade20. While both Axl and Mertk are considered to be involved in efferocytosis and suppression of inflammation, a recent report raises the possibility that they may play opposing roles in certain inflammatory settings, such as that seen in a mouse model of nephrotoxic serum-induced glomerulonephritis21. Because that study was conducted using holo-Axl KO and holo-Mertk KO, the specific cell types that are responsible for these opposing effects remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%